Efeitos da temperatura e do potencial hidrogeniônico em processo de degradação de óleo diesel e de produção de bioemulsificantes por Candida lipolytica UCP 0988 em água do mar. - Silva, Israel Gonçalves Sales da (2019)
The yeast Candida lipolytica UCP 0988 was able to degrade diesel oil and produce bioemulsifiers (BE) with application potential in environmental bioremediation. The effects of pH and temperature variation on the biodegradation efficiency of total petroleum hydrocarbons (TPH) - in the process of biodegradation of B10 S10 diesel oil (10% biodiesel, maximum sulfur content of 10 ppm), with a concentration of 20% (v/v) in seawater by Candida lipolytica UCP 0988 - were investigated by means of a 22 full factorial design, consisting of seven tests, including two replicates of the central point. A linear model was developed including interactions between pH and temperature, indicating the proximity of a local maximum peak and the need for a second order model to incorporate the curvature effect. Gas Chromatography coupled to Mass Spectrometry was used to determine the biodegradation efficiencies in the assays. The highest biotic removal of TPH (39.52%) was obtained, after 15 days, in a test performed at pH 3 and temperature 28ºC (monitored salinity of 40 ‰). Comparison of the residual oil chromatogram of this assay with that of the abiotic assay showed that only hydrocarbons with C7 to C9 chains (such as BTEX) and the C17 to C21 chains (such as pristane and phytane) were not completely degraded by yeast. To evaluate the emulsifying activity of the biosurfactant produced, emulsions were prepared and analyzed by optical microscopy after 0, 24 and 96 h. As the aqueous phase of the emulsions was used the metabolic liquid of the assay which showed greater efficiency in the biodegradation of diesel oil; and as the oily phase were used engine oil, diesel oil and corn oil. The highest frequency of droplet diameters occurred around 1 μm, with frequencies ranging around 70%. Droplet diameter frequency micrographs and histograms revealed the behavior of the formed emulsions, suggesting the existence of a direct relationship between biodegradation and the formation of more stable emulsions.